Jejunogastric Intussusception: A Rare Complication of Gastric Surgery - Shanta, Kaniza Kabir; Amin, Mashah Binte (Journal of Enam Medical College, 2021)
Abstract not available J Enam Med Col 2020; 10(2): 126-129